5.9k views
2 votes
7. If 26y - 4 = 68 + 2y , then y=?

User Mrwweb
by
8.2k points

1 Answer

1 vote

Answer:

y = 3

Explanation:

We move all terms to the left:

26y-4-(68+2y)=0

We add all the numbers together, and all the variables

26y-(2y+68)-4=0

We get rid of parentheses

26y-2y-68-4=0

We add all the numbers together, and all the variables

24y-72=0

We move all terms containing y to the left, all other terms to the right

24y=72

y=72/24

y=3

User Belmiris
by
7.3k points

Related questions

asked Jan 26, 2024 42.9k views
Svetlin Mladenov asked Jan 26, 2024
by Svetlin Mladenov
8.3k points
1 answer
1 vote
42.9k views
asked Feb 3, 2024 201k views
Mark Silberbauer asked Feb 3, 2024
by Mark Silberbauer
8.7k points
2 answers
3 votes
201k views